Gaps in Maternal Behavior, Family Support, and Early Childhood Education Participation in the Development of Children Under Five Years: A Stratified Analysis of Urban vs. Rural Settings - Ida Nursanti; Bhisma Murti; Sri Mulyani (Journal of Health Promotion and Behavior, 2026)
Background: The intensity and quality of developmental stimulation provided by mothers, families, and the early childhood education environment determine the developmental outcomes of children under five years of age. Place of residence influences the cultural practices surrounding child-rearing, access to healthcare services, and the availability of facilities that support child development. This study aims to examine maternal stimulation behaviors, family support, and participation in early childhood education on child development based on place of residence (urban vs. rural). Subjects and Method: A cross-sectional study was conducted involving 200 respondents in urban areas and 200 in rural areas. Respondents consisted of mother-child pairs with children under five years of age, selected according to predetermined criteria. Data were measured using questionnaires and observation sheets (DDST II). Stratified tests were performed using STATA 13 software. Results: In the rural group, positive maternal behavior and family support were significantly associated with improved developmental outcomes for children under five years of age (RR 1.94; 95%CI 1.31 to 2.87; p = 0.001 and RR 1.47; 95%CI 1.17 to 1.867; p = 0.001), while non-significant associations were found in the urban group (p = 0.256 and p = 0.069). In the urban group, children's participation in early childhood education programs was significantly associated with more optimal developmental outcomes (RR 1.59; 95%CI 1.04 to 2.43; p = 0.033), whereas a non-significant association was observed in the rural group (p = 0.546). Conclusion: The factor of place of residence determines differences in maternal behavior, family support, and participation in early childhood education regarding child development. Health promotion intervention research aimed at enhancing maternal behavior and family support for child development needs to be designed with different methodologies based on the residential area.